2020
DOI: 10.2217/cer-2019-0142
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled clinical trial of a hypothermically stored amniotic membrane for use in diabetic foot ulcers

Abstract: Aim: Determine the effectiveness of hypothermically stored amniotic membrane (HSAM) versus standard of care (SOC) in diabetic foot ulcers (DFUs). Methods: A randomized controlled trial was conducted on 76 DFUs analyzed digitally. Results: Cox wound closure for HSAM (38 wounds) was significantly greater (p = 0.04) at weeks 12 (60 vs 38%), and 16 (63 vs 38%). The probability of wound closure increased by 75% (Hazard Ratio = 1.75; 95% CI: 1.16–2.70). HSAM showed >60% reductions in area (82 vs 58%; p = 0.02) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 37 publications
2
44
0
1
Order By: Relevance
“…Then, detailed evaluation of full texts resulted in the removal of 34 articles for the following reasons: were reviews (n = 23); were not RCTs (n = 7); was a duplicate study (n = 1) 26 ; ST was not used as control treatment (n = 3) 27‐29 . Finally, nine studies were eligible for this meta‐analysis 18,30‐37 . The study 34 published by Zelen et al in 2016 was an extension of their previous study 31 published in 2015.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Then, detailed evaluation of full texts resulted in the removal of 34 articles for the following reasons: were reviews (n = 23); were not RCTs (n = 7); was a duplicate study (n = 1) 26 ; ST was not used as control treatment (n = 3) 27‐29 . Finally, nine studies were eligible for this meta‐analysis 18,30‐37 . The study 34 published by Zelen et al in 2016 was an extension of their previous study 31 published in 2015.…”
Section: Resultsmentioning
confidence: 99%
“…Only four studies 31,34,35,37 reported allocation concealment. Participants and personnel in most studies 18,30,31,33,34,36,37 were aware of group assignment while outcome assessors were blinded to group assignment in six studies 30,31,34‐37 . For attrition bias and reporting bias, all studies were considered to have a low risk.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations